2010
DOI: 10.1227/01.neu.0000374870.46963.bb
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception of Combined Awake Brain Tumor Surgery and Intraoperative 1.5-T Magnetic Resonance Imaging

Abstract: Although the combination of awake craniotomy and intraoperative MRI is demanding, it was both tolerable and reasonable for the patients. Our data confirm that intraoperative MRI appears to have no additional significant impact on the subjective patient perception, although it does prolong the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
2
45
0
4
Order By: Relevance
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,[11][12][13][14]18,[22][23][24] In some earlier work we showed that intraoperative multimodality electrophysiological mapping can be seamlessly incorporated into high-field iMRI for tumor resections. 15 Initially when we started the procedure of combining awake craniotomy with high-field iMRI, there were a number of challenges to overcome, including patient comfort and position as well as new draping and anesthetic techniques unique to the iMRI environment.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,12,13,24 In the series described by Leuthardt et al 11 and the case report by Parney et al, 13 an overhead moveable magnet was used for scanning. However, in the other series, 3,12,24 including ours, the position of the magnet was fixed on the floor, and the patient was moved toward the scanner for intraoperative scans. The overall operative time in our patient population was 7.3 hours, which is longer than the times reported in the other published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also enhance the rate of complete tumor resection by providing surgeons with updated information, allowing them to precisely localize tumor remnants intraoperatively and guide their resection accordingly. 10,17,21,25,31,36 Specifically, the application of iMRI for patients with glioma continues to expand because it can enable maximal resection while maintaining the integrity of uninvolved brain tissue. 12,17,36 Nonetheless, as depicted in a recent Cochrane Review, first-level evidence for the clinical applications of such expensive technologies is still lacking and there is no clear answer with regard to the overall benefit in terms of survival and quality of life (QOL).…”
mentioning
confidence: 99%
“…Goebel, Nabavi, Schubert and Mehdorn (2010) reported that satisfaction with the awake craniotomy was high in 24 out of 25 participants. However similarly to Whittle et al (2005) authors failed to address the 39% of participants, reported in the results, who described minor to moderate difficulties.…”
Section: Patient Experience Of Awake Craniotomymentioning
confidence: 99%